Interest of Denosumab for the Treatment of Giant-cells Tumors and Aneurysmal Bone Cysts of the Spine. About Nine Cases. Issue 11 (1st June 2016) - Dubory, Arnaud; Missenard, Gilles; Domont, Julien; Court, Charles
Abstract : Study Design: A prospective cohort study. Objective: The aim of this study was to evaluate the interest of denosumab in the treatment of spinal giant-cells tumors (GCTs) and aneurysmal bone cysts (ABCs). Summary of Background Data: To treat GCTs and ABCs, surgical resection remains the best treatment to limit local recurrence (LR) but constitutes an aggressive treatment with potential morbidity. Denosumab, a human antibody anti-RankL, inhibiting the differentiation of osteoclasts, could be an alternative treatment to avoid aggressive surgery. Methods: Patients suffering from GCTs and ABCs of the spine were included. Patients received a monthly subcutaneous injection of denosumab (120 mg) during a minimum of 6 months either as a neoadjuvant or as an adjuvant therapy. In association with denosumab, an osteosynthesis was added in case of vertebral fracture and a laminectomy in case of spinal cord compression. Clinical and computed tomography (CT)-scan outcomes were analyzed. Results: Eight GCTs and one ABC were included. The mean age was 35 years (range: 22–55 yr). Five patients had neurologic deficit. All patients were operated: six osteosynthesis, one "en bloc" resection, four curettages, and two of them associated with an osteosynthesis. Average duration of denosumab therapy was 12.9 months (range: 3.2–24 months). Among them, four patients began denosumab 6 months at least before the surgery. With a mean follow-up of 19.3 months (range: 3.2–52.4 months), back pain and neurologic deficit improved for all patients. Systematic CT-scan at 6 months showed decrease of tumor size and bone consolidation. Regarding patients treated by neoadjuvant denosumab treatment, intraoperative histologic analysis showed an absence of giant cells and a maximum of 10% of alive tumor cells. Conclusion: Denosumab allows bone formation and tumor regression with a maximum efficacy after 6 months of treatment without widely substituting surgery. Long-term results are mandatory to confirm the interest of denosumab and to evaluate LR when stopping denosumab. Level of Evidence: 3